2008
DOI: 10.3855/jidc.225
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of plasmid-mediated multidrug resistance in epidemic and non-epidemic strains of Salmonella enterica serotype Typhi from Jordan

Abstract: Background: Enteric fever caused by Salmonella enterica serovar Typhi has not been adequately explored in Jordan. Methodology: In this study we investigated antibiotic resistance patterns and resistance determinants coupled with fingerprint methods of forty-eight isolates of S. Typhi obtained from 113 patients with suspected enteric fever admitted at six governmental hospitals in different directorates in Jordan. Twenty-four isolates were from an outbreak of typhoid fever that occurred between October 2004 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…S. Typhi exists as a Gram-negative encapsulated, flagellated, facultative anaerobic bacilli. It possesses three major antigens: H or flagellar antigen, O or somatic antigen, and Vi antigen [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…S. Typhi exists as a Gram-negative encapsulated, flagellated, facultative anaerobic bacilli. It possesses three major antigens: H or flagellar antigen, O or somatic antigen, and Vi antigen [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…The standardised protocol for H58 detection and subtyping was applied to screen 99 S. Typhi strains of unknown haplotype, isolated as part of three independent investigations from blood cultures of hospitalized patients suffering typhoid fever in Jordan ( Al-Sanouri et al 2008), India and Pakistan (unpublished results). Previous characterization of these strains showed that 74 of them (75%) were MDR (resistant to ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole), of which 39 were additionally resistant to nalidixic acid (Table 3).…”
Section: S Typhi Isolates Tested In This Studymentioning
confidence: 99%